Survey, Question, Read, Recite, Review (SQ3R) Method Improves Reading Comprehension of Descriptive Texts for Tenth Grade Students: Metode Survey, Question, Read, Recite, Review (SQ3R) Meningkatkan Pemahaman Membaca Teks Deskriptif untuk Siswa Kelas Sepuluh - Juni Adi Saputra; Kurnia Febianti; Tri Rohani (Universitas Muhammadiyah Sidoarjo, 2025)
Background (General & Specific): Reading is an important skill in English learning that is often challenging for students, especially in understanding descriptive texts. Knowledge Gap: However, the effectiveness of learning strategies such as the SQ3R method in the context of secondary school students' reading comprehension remains under-researched empirically. Aim: This study aims to evaluate the effectiveness of SQ3R (Survey, Question, Read, Recite, Review) method in improving reading comprehension of grade X students at SMA Negeri 1 Pajar Bulan. Methods & Results: Using a quasi-experimental design, two groups of students were compared: an experimental group that received instruction with the SQ3R method and a control group with the conventional method. Results showed a significant increase in the experimental group's reading comprehension score (mean 67.13) over the control group (mean 44.55), based on paired and independent t-tests. Novelty: This study shows that SQ3R effectively strengthens students' ability to summarize text content, find specific information, and understand vocabulary. Implications: The findings indicate that the integration of SQ3R strategy in reading instruction can be an effective pedagogical approach to improve students' reading comprehension in an active and structured manner.Highlights: Enhances critical reading through structured stages (Survey to Review). Demonstrates significant improvement in students' test scores. Supports vocabulary and detail identification in descriptive texts. Keywords: SQ3R Method, Reading Comprehension, Descriptive Text, English Education, Experimental Study